Apuntes para una historia de la Ley del contrato de seguro del Perú - Meza Carbajal, Luis Alberto (Revista de Derecho, 2019)
This study refers to the historical process that gave rise to the Peruvian Insurance Contracts Act 2012 (ica). It aims to identify the proposals and performance of the stakeholders that preceded this important piece of legislation. To that end, documents from the Peruvian Congress and other sources are mainly used. Among its conclusions, it states that unlike previous proposals the focus of the project that gave rise to the ica, that is, the sbs Project 2005, was the need to protect the insured party and promote legal balance in insurance relationships, based on the Stiglitz Project and contributions from local experts and organizations. It also identifies the participation of stakeholders, their positions and proposals. Finally, the studyrecommends that Draft Law 4635/2014-cr, which seeks the exclusion of the socalled “gross risks” from the scope of the ica 2012, should not be approved by the Peruvian Congress.